Management Audit in Public Finance Entities - Nowak, Edward (Kontrola zarządcza w jednostkach sektora finansów publicznych, 2011)
he paper concerns the system of management audit in public finance entities. The origin and essence of management audit in public finance are presented, as well as the standards for management audit developed by the Minister of Finance. Management audit is also demonstrated as a management function. Problems with creating and improving systems of management audit in public finance entities are indicated against this background.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 107-115
Keywords: public finance; finance entities; management audit